Konsumsi tuak mempengaruhi terjadinya erosi gigi di Kecamatan Maiwa Kabupaten Enrekang (Palm wine consumption affects the incidence of dental erosion in Maiwa, Enrekang) - Rizky Noviyanti; Indrya Kirana Mattulada (DiscoverSys Inc., 2014)
Palm wine from the palm is a typical drink of Maiwa, Enrekang. Bitter palm wine taken from fermented fruit of sugarplant intercepts (Arenga pinnata) which is called sap. Excessive drinking palm wine can cause pathological effects inthe oral cavity, because the Palm wine have acidic pH that can affect the occurrence of dental erosion. The purpose ofthis study was to determine the effect of palm wine consumption on the occurrence of dental erosion. Thisobservational analytic with cross sectional approach showed that from 100 samples, 75 people had suffered dentalerosion due to bitter palm wine consumption and 25 people did not suffer dental erosion because they consumed sweetpalm wine only. So, it was concluded that palm wine consumption affects the dental erosion in Maiwa, Enrekang.